2018
DOI: 10.1128/mbio.01279-18
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Analysis in Absence of Major EffectorATF1Unveils Novel Components in Yeast Flavor Ester Biosynthesis

Abstract: Basic research with laboratory strains of the yeast Saccharomyces cerevisiae has identified the structural genes of most metabolic enzymes, as well as genes encoding major regulators of metabolism. On the other hand, more recent work on polygenic analysis of yeast biodiversity in natural and industrial yeast strains is revealing novel components of yeast metabolism. A major example is the metabolism of flavor compounds, a particularly important property of industrial yeast strains used for the production of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…We have previously shown that overexpression of the S. cerevisiae EAT1 increased ethyl acetate production in S. cerevisiae (Kruis et al, 2017). These results were confirmed in a study where EAT1 was identified as a source of ethyl acetate synthesis in S. cerevisiae Δ atf1 (Holt et al, 2018).…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…We have previously shown that overexpression of the S. cerevisiae EAT1 increased ethyl acetate production in S. cerevisiae (Kruis et al, 2017). These results were confirmed in a study where EAT1 was identified as a source of ethyl acetate synthesis in S. cerevisiae Δ atf1 (Holt et al, 2018).…”
Section: Introductionsupporting
confidence: 62%
“…This was the most apparent in the case of ethyl acetate and isoamyl acetate, where more than 50% ethyl acetate production remained in some cases (Supplementary Figure S4). Imo32p was previously associated with ester production in the absence of Atf1p (Holt et al, 2018). The single deletion strain CEN.PK2-1D Δ imo32 produced 10% less ethyl acetate in both YSg and YPD-80 media.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The obtained strains are tested for their phenotypes. Thanks to those approaches, genes, mutations, or even translocations have been validated for diverse wine yeast properties, such as lag phase duration, fermentation capacity under nitrogen starvation, and ester production [42,51,52].…”
Section: Qtl Mapping and Backcrossing 21 Identification Of The Molecmentioning
confidence: 99%